الحيل وتطبيقاتها في المعاملات المالية المعاصرة بيع الوفاء نموذجا (دراسة فقهية تحليلية لفتوى الهيئة الشرعية الوطنية لمجلس العلماء الإندونيسي ومجمع الفقه الإسلامي الدولي بشأن اتفاقية إعادة الشراء (الريبو) كتطبيق بيع الوفاء المعاصر) - Ridwan Agustiawan; Trisiladi Supriyanto; Hari Susanto (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze ḥiyal within the framework of contemporary financial transactions, with a focus on bayʿ al-wafā as an applied model. It also sheds light on the fatwas issued by the National Sharia Board of the Indonesian Council of Ulama (DSN-MUI) and the International Islamic Fiqh Academy (IIFA) regarding repurchase agreements as a contemporary application of bayʿ al-wafā . The research adopts an inductive, analytical, and comparative methodology. The study concluded with several key findings, most notably that the disagreement among jurists regarding the use of ḥiyal is primarily verbal. They unanimously agree on the criterion by which ḥiyal is classified as permissible or impermissible: its alignment or conflict with the principles of Islamic law. The disagreement lies in categorizing specific cases under either category, which varies from one case to another. Additionally, the study found that repurchase agreements closely resemble bayʿ al-wafā with no significant differences between them. Both transactions, in reality, represent interest-bearing loans riba , as the sales and purchases involved are not genuine. Thus, they are prohibited because they serve as a stratagem to circumvent riba. The study further highlights that both the National Sharia Board (DSN-MUI) and the International Islamic Fiqh Academy (IIFA) agree on the necessity of aligning repurchase agreements with the principles of Islamic law. However, they differ in their rulings. The DSN-MUI permits such agreements, provided they adhere to specific conditions outlined in its fatwa, while the IIFA prohibits them, considering them transactions tainted with riba ambiguity. The primary difference lies in the methodology of ijtihad and the application of Shariah principles within the context of repurchase agreements.